ANALYSIS OF OCCUPATIONAL HEALTH AND SAFETY RISK USING HIRADC METHOD IN MEDICAL RECORD INSTALLATION AT NGANJUK HOSPITAL - Maulana Muhammad Sirojuddin Abbas; Dian Herawati (Journal of Health Policy and Management, 2024)
ABSTRAK Background : Hospitals are required to organize occupational health and safety (K3RS) in all parts of the installation in the hospital, one of which is the medical record installation. The medical record installation has a storage room, namely a filing room which is an important part of storing medical records and has the potential to have various potential hazards. The management of Nganjuk Hospital for this period has not carried out a risk assessment on the medical record installation section. Subject dan Methods: This research is a qualitative descriptive study with a case study design. The sampling technique used was purposive sampling technique. The subjects used in this study were 2 medical record officers, the Head of the Medical Record Installation, and the Head of the K3 Section of Nganjuk Hospital. Results: Based on the HIRADC matrix, the Nganjuk Hospital medical record installation in the Filing section identified a potential hazard in the Moderate-High risk category, including; dusty filing shelves and medical records, poor environmental conditions (temperature, lighting, humidity), distance and height between shelves is not ergonomic, there are sharp objects (remaining staples) in the medical records, carrying and delivering too many medical records to each poly aim. Conclusion : The potential for danger in the filing room is found to be quite a risk to interfere with the work of the filing officer. This requires risk control, including; carry out elimination, substitution, technical control, administrative control and use of PPE